The role of minimally invasive technologies in the diagnosis and treatment of adhezive intestinal obstruction - I. A. Yusubov (Сибирский научный медицинский журнал)
One of the serious intra-abdominal complications after surgery is intestinal obstruction of adhesion origin (IOAO). Mortality during postoperative intestinal obstruction is 16.2–52.5 %. Aim of the study – laparoscopic diagnosis of IOAO in the early postoperative period and optimization of adhesiolysis.Material and methods. In the early postoperative period 70 patients with IOAO of upper gastrointestinal tract were examined and treated; laparoscopic operation was performed to 46 patients (the main group), an open method (laparotomy) – to 24 patients (the control group).Results and discussion. It was revealed that upper-middle and lower-middle incision laparotomies are more likely to cause intestinal obstruction. The sensitivity of preoperative ultrasound diagnosis of movable visceroparietal adhesions of small intestinal loops is 94.6 %, and the sensitivity of laparoscopic diagnosis is 99.2 %. When using minimally invasive technology, the frequency of intraoperative (4 (8.7 %) and 8 (33.3 %), respectively, p < 0.05) and postoperative complications (5 (10.9 %) and 13 (54.1 %), p < 0.05), mortality (0 and 4 (16.6 %), p < 0.05) and length of stay in hospital (5.7 (3–8) and 14.3 (10–17) days, p < 0,05) was less compared to laparotomy.Conclusions. Using of laparoscopic adhesiolysis and anti-adhesion barrier is appropriate in patients with I-II grade adhesion process. In cases where technical difficulties arise during laparoscopic adhesiolysis, it is more pathogenetically justified to separate adhesions by passing through a mini-laparotomy incision. If this is not possible, it is advisable to perform complex anti-adhesion measures, including conversion to laparotomy and systemic enzymotherapy after adhesiolysis.